Die eigene Lehre erforschen - Lohnt sich der Aufwand? - Josef Wiemeyer (FernUniversität Hagen, 2018)
Digital media do not only offer new options for teaching and learning. In addition, the implementation of digital media often generates data that reveal valuable information concerning learning behavior. Without digital media this data is not available. However, it is hard to interpret these "superficial" data. In this paper the ambivalence of field research in media pedagogy will be illustrated by using four examples (interactivity, self-regulated learning, audience response systems connected with learning games, and pedagogical agents). In this research the well-known limits of field research appeared (e.g., control of conditions, missing randomization, self-selection, confounding); on the other hand, the differential effects of the above-mentioned media and conditions could be revealed. The price that has to be paid for this increase of knowledge concerning the effects of one's own teaching as a useful source of self-improvement is an increased effort concerning staff, material, and time.